Early life determinants of lung function change from childhood to adolescence. (June 2018) - Schultz, Erica S.; Hallberg, Jenny.; Andersson, Niklas; Thacher, Jesse D.; Pershagen, Göran; Bellander, Tom; Bergström, Anna; Kull, Inger; Guerra, Stefano; Thunqvist, Per.; Gustafsson, Per M.; Bottai, Matteo; et al.
Abstract: Rationale: Little is known about how perinatal and childhood factors influence lung function change between childhood and adolescence. Objectives: To investigate possible early life predictors of change in FEV1 between age 8 and 16 years. In addition, to investigate possible predictors of having persistently low lung function (FEV1 <25th percentiles both at age 8 and 16) up to adolescence. Methods: The BAMSE birth cohort study collected data throughout childhood on environmental factors, individual characteristics, and spirometric measures at 8 and 16 years (n = 1425). Associations between early life predictors (n = 31) and FEV1 increase between 8 and 16 years were assessed with linear regression. Predictors of having persistently low lung function were examined. Results: Few factors were consistently associated with altered lung function growth, although low birth weight, asthma heredity (paternal), secondhand smoke in infancy, and season of birth had a significant impact (p-value ≤0.01). The majority of subjects stayed however within the same category of lung function between ages 8 and 16 years (in total 821/1425 = 58%). Predictors associated with having persistently low lung function were gestational age, secondhand smoke (at 2 and 8 years of age), and factors related to lower respiratory tract infections in infancy. Conclusions: In summary, rather few exposures in childhood were identified to have a significant impact on lung function growth between childhood and adolescence. Our data support previous study findings indicating that lung function development is influenced by factors before birth and in infancy, including second hand tobacco smoke. Highlights: Associations between early life factors and lung development were assessed in a cohort. Birth weight, asthma heredity and secondhand smoke affected FEV1 growth. FEV1 growth was not related to any environmental factor after the first year of life. Low FEV1 at both 8 and 16 years was also associated with secondhand smoke.